A genome‐wide association study in Caucasian women suggests the involvement of HLA genes in the severity of facial solar lentigines. (8th August 2016) - Laville, Vincent; Clerc, Sigrid Le; Ezzedine, Khaled; Jdid, Randa; Taing, Lieng; Labib, Taoufik; Coulonges, Cedric; Ulveling, Damien; Carpentier, Wassila; Galan, Pilar; Hercberg, Serge; Morizot, Frederique; et al.
Summary: Solar lentigines are a common feature of sun‐induced skin ageing. Little is known, however, about the genetic factors contributing to their development. In this genome‐wide association study, we aimed to identify genetic loci associated with solar lentigines on the face in 502 middle‐aged French women. Nine SNPs, gathered in two independent blocks on chromosome 6, exhibited a false discovery rate below 25% when looking for associations with the facial lentigine score. The first block, in the 6p22 region, corresponded to intergenic SNPs and also exhibited a significant association with forehead lentigines (P = 1.37 × 10 −8 ). The second block, within the 6p21 HLA region, was associated with decreased HLA‐C expression according to several eQTL databases. Interestingly, these SNPs were also in high linkage disequilibrium with the HLA‐C*0701 allele ( r 2   = 0.95). We replicated an association recently found by GWAS in the IRF4 gene. Finally, a complementary study on 44 selected candidate SNPs revealed novel associations in the MITF gene. Overall, our results point to several mechanisms involved in the severity of facial lentigines, including HLA/immunity and the melanogenesis pathway.